Rekayasa Perangkat Lunak Sistem Informasi Penjualan Barang Funiture Secara Online dengan menggunakan Metode Prototyping - Aenun Nisa; Dandi Ramdani; Galih Haryanto; Winni Maeylani; Sri Mulyati; Yulianti Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
KANA Furniture shop is engaged in the sale of home decorations. At this time the system used is a manual system, where every customer who wants to make a purchase must come to the store. Using a system like this can hinder the buying process by customers. From the problems that occur in the KANA FURNITURE Store, the author makes an online furniture sales information system that is tested with the Prototyping Method. The prototyping method is a software development test to simulate a program carried out by the developer and can be directly evaluated by the user in terms of program making. The results of making this online sales application are expected that the company can help customers who want to shop remotely and can also provide sales information related to product names and prices to customers and can facilitate sales transactions and expand business networks.